1997
DOI: 10.1088/0963-0252/6/2/013
|View full text |Cite
|
Sign up to set email alerts
|

High-density plasma production using a slotted helical antenna at high microwave power

Abstract: This paper presents results of high-density plasma production experiments carried out using an optimally designed and excited slotted helical antenna. The slotted helical antenna was excited by linearly polarized, right-hand polarized (RHP) and left-hand polarized (LHP) CW microwaves (f = 2.45 GHz) with power up to 2.5 kW. Two different discharges-the resonant and the non-resonant discharges-were studied. In the resonant discharges the magnetic field at the edge of the helical antenna was equal to the ECR fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
(58 reference statements)
3
22
0
Order By: Relevance
“…One may improve the situation somewhat by using a magnetic mirror configuration as used in authors' work on electron cyclotron resonance and helicon plasma production. [46][47][48][49][50] Therefore, for the present experiments, use of a magnetic mirror configuration has been necessary for trapping the population of nonthermal electrons.…”
Section: Motivation and Approachmentioning
confidence: 99%
“…One may improve the situation somewhat by using a magnetic mirror configuration as used in authors' work on electron cyclotron resonance and helicon plasma production. [46][47][48][49][50] Therefore, for the present experiments, use of a magnetic mirror configuration has been necessary for trapping the population of nonthermal electrons.…”
Section: Motivation and Approachmentioning
confidence: 99%
“…[1][2][3][4] We have already reported the experiments, 5 which indicated that the electric field strength of the extraordinary wave ͑the X wave͒ was small around the center of the uniform plasma, and became large at the radial edge of the plasma. Furthermore, recent numerical results [6][7][8] show evidence for the propagation or, absorption of the lefthanded circularly polarized wave ͑the L wave 9 ͒ or other modes in the ECR plasma even on the condition; that the magnetic field strength is greater than the ECR condition (/ ce Ͻ1) or that the electron plasma frequency is higher than the wave frequency (/ pe Ͻ1). Recently, electromagnetic waves that propagate up to the outside ECR region have been giving some attention in a numerical simulation for plasma processing.…”
Section: Yoko Ueda A) Hiroshi Muta B) and Yoshinobu Kawaimentioning
confidence: 99%
“…[2][3][4] While the first two populations are isotropic 13 with T r ϭT ʈ /T Ќ Ϸ1[T ʈ (T Ќ ): parallel ͑perpendicular͒ temperature͔, the warm electron population is anisotropic. Although a small warm electron component is not expected to influence significantly the nature of the guided modes in a plasma-loaded guide, the present study does include two electron populations ͑without any restrictions on their isotropicities and densities͒ keeping future applications in mind.…”
Section: A Plasma Field Equationsmentioning
confidence: 99%